2023
DOI: 10.1002/mana.202100601
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic problem involving logarithmic weight under exponential nonlinearities growth

Abstract: In this paper, we study the nonlinear weighted elliptic problem where B is the unit ball of , , and the singular logarithm weight with the limiting exponent in the Trudinger–Moser embedding. The nonlinearities are critical or subcritical growth in view of Trudinger–Moser inequalities. We prove the existence of nontrivial solutions via the critical point theory. In the critical case, the associated energy functional does not satisfy the compactness condition. We give a new growth condition and we point out it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To be more specific, the authors demonstrated the existence of positive solutions for the above problem by combining variational techniques with regularity arguments. Alternatively, [4,10,11,14,19,20,43] investigated elliptic equations with weighted N-Laplacian operator and critical Trudinger-Moser nonlinearities, while this paper will focus on a different class of problems.…”
Section: Introductionmentioning
confidence: 99%
“…To be more specific, the authors demonstrated the existence of positive solutions for the above problem by combining variational techniques with regularity arguments. Alternatively, [4,10,11,14,19,20,43] investigated elliptic equations with weighted N-Laplacian operator and critical Trudinger-Moser nonlinearities, while this paper will focus on a different class of problems.…”
Section: Introductionmentioning
confidence: 99%